International competence and knowledge studies and attitudes of the Brazilian Management accountant: analyses and reflections - Ricardo Lopes Cardoso; Octavio Ribeiro Mendonça Neto; José Carlos Oyadomari (BBR: Brazilian Business Review, 2010)
The main purpose of this study is to understand what the competences of the Management accountant are, compare to international studies and assess the existence of competences to be prioritized. This questioning has as motivation the placements of Hardern (1995), Morgan (1997), IMA (1996 e 1999) and IFAC (2003). The theoretical basis about competences is related to McClelland study (1973, 1998), Boyatzis (1982) and Spencer and Spencer (1993). This research is based on the study of 18 competences about knowledge, skills and attitudes obtained in accountant literature and that have been submitted to 200 Management accountants. Data collection instrument presented a 0.884 Cronbach Alpha. From a factorial analysis and after Kruskal-Wallis test 12 competences were obtained as the most relevant segregated in 3 factors, in comparison to international studies of nine common competences 4 were not considered relevant in statistical tests and only one must be prioritized. Results demonstrate differences between competences required from Brazilian Management accountants and from other countries, being that their reasons is an open-ended question up to the moment.